2016
DOI: 10.1103/physrevb.94.134509
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of superconductivity to competing magnetic phases in tetragonal FeS

Abstract: We have determined the superconducting and magnetic properties of a hydrothermally synthesized powder sample of tetragonal FeS using muon spin rotation (µSR). The superconducting properties are entirely consistent with those of a recently published study, showing fully gapped behavior and giving a penetration depth of λ ab = 204(3) nm. However, our zero-field µSR data are rather different and indicate the presence of a small, non-superconducting magnetic phase within the sample. These results highlight that sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
1
11
2
Order By: Relevance
“…1f). Furthermore, due to the complex de-intercalation procedure to prepare FeS, other byproducts could form [38]. Recently, a quantum oscillations study suggested that FeS has a 3D Fermi surface [20], not supported by the current ARPES studies.…”
mentioning
confidence: 69%
“…1f). Furthermore, due to the complex de-intercalation procedure to prepare FeS, other byproducts could form [38]. Recently, a quantum oscillations study suggested that FeS has a 3D Fermi surface [20], not supported by the current ARPES studies.…”
mentioning
confidence: 69%
“…The temperature dependence of all four modes is governed by the contraction of the lattice, but shows anomalies at 50 K and below 20 K. The anomaly observed at 20 K has a correspondence in the thermal expansion 20 and µSR experiments 21,22 which indicate short-range magnetic order. The long-range magnetic order observed recently by neutron diffraction experiments 41 below T N =116 K has no correspondence in the Raman spec-tra.…”
Section: Discussionmentioning
confidence: 90%
“…Phonon energy (cm −1 ) Atomic displacement Calculation Experiment However, the anomaly at 20 K coincides with the emergence of short range magnetic order as inferred from two µSR studies. 21,22 Susceptibility measurements on a sample from the same batch were inconclusive. On the other hand, the XRD data show a small anomaly in the lattice parameters, and the unit cell volume does not saturate at low temperature but rather decreases faster between 20 K and 10 K than above 20 K. 20 This volume contraction by and large reproduces the change in the phonon energies as can be seen by closely inspecting the lowtemperature parts of Fig.…”
Section: Symmetrymentioning
confidence: 99%
“…Below 70 K the diffusion slows down and the depolarization rate in ZF data saturates around B ∼ 0.35 μs −1 [18]. Depolarization due to diluted magnetic impurities [24] can be excluded since in this case the muons stopping at site A should be also affected by stray fields. However, we did not find any noticeable static contribution to the depolarization rate of site A.…”
mentioning
confidence: 99%